Exploring The Views of Malaysian Hoteliers About Survival During the Covid-19 Pandemic - Tay, Kai Xin; Nordin, Nur Hidayah; Lim, Le Xian (UUM Press, 2024)
The sudden new crown pneumonia epidemic has had a huge impact on tourism, as well as hospitality industry in Malaysia. This paper analyses the views and reaction in crisis management practices pursued by hotel managers for business survival during the COVID-19 pandemic. To do so, in-depth interviews were carried out on the managers of Malaysian hotels (five managers from 3-star hotels, and four managers from 5-star hotels). The results indicated that the labour actions (e.g., unpaid leave, salary cut and layoff) were the first and most favour by hotels to respond to the COVID-19. However, it causes the shortage of manpower when the hospitality industry resumes back at the recent stage. This is one of the main challenges faced by hoteliers. Digital marketing and promotion were another strategy implemented by hotels to increase occupancy rate during the pandemic. In addition, views on government supports to the hotels during the pandemic were also identified.